The use of adhesion sutures to minimize the formation of seroma following mastectomy with immediate breast reconstruction - Marcela Caetano Cammarota; Ismar Ribeiro Junior; Rafael Quaresma de Lima; Conrado Miranda de Almeida; Luciano Gomes de Moura; Leonardo Martins Costa Daher; Daniel Augusto dos Santos Soares; Milena Carvalho Almeida Galdino; José Carlos Daher; Fabrício Tavares Mendonça (Revista Brasileira de Cirurgia Plástica)
INTRODUCTION: Breast cancer is the most common cancer among women in Brazil. With the advent of immediate breast reconstruction, several techniques with many benefits for patients were introduced, including the use of alloplastic materials. A seroma is a frequent complication in all surgical procedures, and several methods have been developed to prevent it, which include the use of vacuum suction drains and adhesion sutures, as proposed by Baroudi. This study aims to demonstrate the advantages of the use of adhesion sutures between subcutaneous tissue and the muscle flap in breast reconstruction using implants or expanders after mastectomy. METHODS: Patients who underwent breast reconstruction using implants or expanders after mastectomy were followed up for 5 months . Patients were divided into a control group treated without adhesion sutures, and a Baroudi group treated with adhesion sutures. RESULTS: A statistically significant difference was observed with the use of adhesion sutures, with a lower incidence of seroma, reduced drain permanence, less need to return to the clinic, and faster recovery. There was no increase in surgical complications. CONCLUSION: The use of adhesion sutures in breast reconstruction is an effective option that reduces the occurrence of seroma and associated complications, resulting in faster recovery and return to normal activities.